1999
DOI: 10.1074/jbc.274.47.33227
|View full text |Cite
|
Sign up to set email alerts
|

A Site-specific, Membrane-dependent Cleavage Event Defines the Membrane Binding Domain of FtsY

Abstract: Targeting of many polytopic proteins to the inner membrane of prokaryotes occurs via an essential signal recognition particle-like pathway. Unlike the general secretory pathway, the proteins involved in this pathway and their activities appear in many respects to mirror closely those of their eukaryotic homologues. However, the Escherichia coli signal recognition particle receptor, FtsY, differs significantly at the amino terminus from the eukaryote homologue ␣-subunit of the signal recognition particle recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 42 publications
(42 reference statements)
2
48
1
Order By: Relevance
“…20). This proposal has been confirmed several times by demonstrating that FtsY assembles on membranes via interactions with a trypsin-sensitive component (22,37). Finally, the most compelling evidence for FtsYmembrane protein association has recently been offered by studies of the interaction between FtsY and the SecYEG complex in E. coli (11,12).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…20). This proposal has been confirmed several times by demonstrating that FtsY assembles on membranes via interactions with a trypsin-sensitive component (22,37). Finally, the most compelling evidence for FtsYmembrane protein association has recently been offered by studies of the interaction between FtsY and the SecYEG complex in E. coli (11,12).…”
Section: Discussionmentioning
confidence: 54%
“…Nevertheless, various studies have suggested that FtsY functions as a membrane-bound receptor (18,19). Interestingly, A-domain-truncated FtsY versions exhibit strong affinity for membrane lipids (20,21), possibly through the N-domain (22), an interaction that seems to be dominated by electrostatic forces (21). However, the precise lipid-interacting domain in FtsY has not been defined, and the mechanism and functional role of lipid binding to the receptor remain elusive.…”
mentioning
confidence: 99%
“…Membrane Flotation Experiments-Ultracentrifugal sedimentation experiments were carried out in a bench-top ultracentrifuge (TLX120 Optima; TLA120.2 rotor; Beckman), using polypropylene tubes (0.2 ml) as described (34,35). Reactions (15 l in buffer B (50 mM Tris-Cl, pH 8, 50 mM KCl, 5 mM MgCl 2 )) containing SecA or SecA⌬Bulb (0.5 g) in the presence or absence of inner membrane vesicles (IMVs) (Յ3 g) and proOmpA-His (0.12 g) (36) were adjusted to 1.74 M final sucrose concentration and deposited at the bottom of the tube.…”
Section: Methodsmentioning
confidence: 99%
“…SecA PBD Mutants Bind to SecYEG-containing Membranes-To examine the effect of PBD mutations on the ability of SecA to bind to SecYEG and to form the translocase ternary complex, we employed membrane flotation (34,35). Inverted IMVs, treated with urea to remove endogenous SecA (19), were loaded at the bottom of a sucrose gradient (corresponding to lanes 7-9 in Fig.…”
Section: -7)mentioning
confidence: 99%
“…58 The structural and functional implications of these interactions have recently been discussed 56 -in the intact FtsY they may couple the putative targeting function of the N-terminal A-domain (or perhaps, the N1 helix itself) to the NG GTPase domain. 12,26,59 That a similar orientation of the C-terminal helix is maintained in the structure of T. aquaticus FtsY, despite the first 20 amino acids of the NG domain being absent (see above), is explained by a crystal packing interaction that compensates-although much of the linker peptide between the N-and G-domains is disordered, residues 83-94 can be located unambiguously in the electron density map, splayed across a crystal contact to pack at the N/ G interface of an adjacent monomer [ Fig. 3(B)].…”
Section: A Common Arrangement Of the N And C Terminus Prior To Assemblymentioning
confidence: 99%